Associations of body mass index at different ages with early-onset colorectal cancer - Li, Hengjing; Boakye, Daniel; Chen, Xuechen; Jansen, Lina; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Gastroenterology, 2022)
BACKGROUND & AIMS: Incidence of colorectal cancer (CRC) in younger adults is increasing in many countries. Given the established association of body mass index (BMI) with CRC risk and the increasing obesity prevalence among younger generations, we aimed to evaluate the association of BMI at different ages during early adulthood with early-onset CRC. METHODS: Among 6602 patients with CRC and 7950 matched controls who were recruited in 2003-2020 in the Darmkrebs: Chancen der Verhutung durch Screening study, a population-based casecontrol study from Germany, 747 patients and 621 controls were younger than 55 years and included in this analysis. Selfreported height and weight at ages 20 years and 30 years and at approximately 10 years before diagnosis or interview were recorded in personal interviews. Associations of BMI with early-onset CRC were estimated using multiple logistic regression. RESULTS: Compared with participants with BMI <25 kg/m(2), those with BMI >= 30 kg/m(2) (obesity) at ages 20 years and 30 years and approximately 10 years before diagnosis or interview had 2.56- (95% confidence interval, 1.205.44), 2.06- (confidence interval, 1.25-3.40), and 1.88- (95% confidence interval, 1.30-2.73) fold risk of early-onset CRC. The association of BMI with early-onset CRC risk was particularly pronounced among, and essentially restricted to, the majority of participants with no previous colonoscopy. CONCLUSIONS: Obesity at early adulthood is strongly associated with increased risk of early-onset CRC. German Clinical Trials Register ID: DRKS00011793.